The frozen elephant trunk technique for the treatment of extensive aortic aneurysms: operative results and follow up - Karck, Matthias; Chavan, Ajay; Khaladj, Nawid; Friedrich, Holger; Hagl, Christian Matthias; Haverich, Axel (European journal of cardio-thoracic surgery, 2005)
OBJECTIVE: The 'frozen' elephant trunk technique allows for single-stage repair of combined aortic arch and descending aortic aneurysms using a 'hybridprosthesis' with a stented and a non-stented end. This report summarizes the operative- and follow-up data (mean follow-up 14 months) with this new treatment. - METHODS: Between 09/01 and 4/04, 22 patients (62+/-9 years; 9 female) with different aortic pathologies (15 aortic dissections, 7 aneurysms) were operated on after approval from the local institutional review board. The stented end of the hybridprosthesis was deployed in the descending aorta through the opened aortic arch during hypothermic circulatory arrest and selective antegrade cerebral perfusion. - RESULTS: All patients survived the procedure but one patient died of acute hemorrhage due to rupture of the false lumen in the descending aorta on the second postoperative day. Two patients required reexploration of the chest for bleeding complications. In 2 of 4 patients who developed neurological dysfunction, symptoms resolved completely. In one of them, the descending aorta was perforated intraoperatively due to misplacement of the stented end of the hybridprosthesis. In all follow-up CT-scans thrombus formation in the descending aortic aneurysm excluded by the stented end of the hybridprosthesis has been observed. - CONCLUSIONS: This procedure is performed through median sternotomy and combines the concepts of the elephant trunk operation and endovascular stenting of descending aortic aneurysms. Favourable intraoperative and postoperative results during follow-up with regard to thrombus formation around the stented descending aortic segment encourage us to evaluate all patients with thoracic aneurysms extending to proximal and distal of the left subclavian artery for this treatment.
Gesehen am 01.09.2016